Active biomaterials for mechanobiology. (January 2021) - Özkale, Berna; Sakar, Mahmut Selman; Mooney, David J.
Abstract: Active biomaterials offer novel approaches to study mechanotransduction in mammalian cells. These material systems probe cellular responses by dynamically modulating their resistance to endogenous forces or applying exogenous forces on cells in a temporally controlled manner. Stimuli-responsive molecules, polymers, and nanoparticles embedded inside cytocompatible biopolymer networks transduce external signals such as light, heat, chemicals, and magnetic fields into changes in matrix elasticity (few kPa to tens of kPa) or forces (few pN to several μN) at the cell-material interface. The implementation of active biomaterials in mechanobiology has generated scientific knowledge and therapeutic potential relevant to a variety of conditions including but not limited to cancer metastasis, fibrosis, and tissue regeneration. We discuss the repertoire of cellular responses that can be studied using these platforms including receptor signaling as well as downstream events namely, cytoskeletal organization, nuclear shuttling of mechanosensitive transcriptional regulators, cell migration, and differentiation. We highlight recent advances in active biomaterials and comment on their future impact.